2017
DOI: 10.1111/tpj.13761
|View full text |Cite
|
Sign up to set email alerts
|

Upstream kinases of plant SnRKs are involved in salt stress tolerance

Abstract: SummarySucrose non‐fermenting 1‐related protein kinases (SnRKs) are important for plant growth and stress responses. This family has three clades: SnRK1, SnRK2 and SnRK3. Although plant SnRKs are thought to be activated by upstream kinases, the overall mechanism remains obscure. Geminivirus Rep‐Interacting Kinase (GRIK)1 and GRIK2 phosphorylate SnRK1s, which are involved in sugar/energy sensing, and the grik1‐1 grik2‐1 double mutant shows growth retardation under regular growth conditions. In this study, we es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 55 publications
0
49
0
1
Order By: Relevance
“…Since GRIK kinases also regulate kinases that mediate sugar sensing, this mechanism represents a potential novel interconnection of salt stress and energy status of plants (Barajas‐Lopez et al . ).…”
Section: Salt Overly Sensitive – From a Pathway To A Networkmentioning
confidence: 97%
See 1 more Smart Citation
“…Since GRIK kinases also regulate kinases that mediate sugar sensing, this mechanism represents a potential novel interconnection of salt stress and energy status of plants (Barajas‐Lopez et al . ).…”
Section: Salt Overly Sensitive – From a Pathway To A Networkmentioning
confidence: 97%
“…Furthermore, it was shown that the sos2 phenotype could not be complemented by a non-phosphorylatable T168A version of SOS2. Since GRIK kinases also regulate kinases that mediate sugar sensing, this mechanism represents a potential novel interconnection of salt stress and energy status of plants ( Barajas-Lopez et al 2018).…”
Section: Salt Overly Sensitive -From a Pathway To A Networkmentioning
confidence: 99%
“…Lee et al (2007) has suggested the possibility of CBL1 and CBL9 to be the interacting partners of CIPK16. More recently, the ability of other kinases, such as GRIK kinases, to release the auto-inhibitory state of SOS2 has been established ( Barajas-Lopez et al 2018). This implies that there could be an alternative interactome for CIPKs apart from the well-known CBLs to release it from its' auto-inhibitory form.…”
Section: Effect Of Atcipk16 Transgene In Salt Stressmentioning
confidence: 99%
“…Salt stress signals may be sensed by "sensor molecules" owing to the salt stress related changes in cytosolic Ca 2+ levels in root cells. These sensor molecules then interact with/phosphorylate AtCIPK16 to release it from the auto-inhibitory state (Barajas-Lopez et al 2018;Sanchez-Barrena et al 2007).…”
Section: The Proposed Model Of Salinity Response In Atcipk16 Transgenicsmentioning
confidence: 99%
“…Stoichiometries of the Na + /H + antiporters and proton pumps (H + /ATP) are critical for models of energy use, as are voltage dependences and conductances of transporters such as VisHKT1 (Henderson et al ., ). Likely interactions of the transport of Na + with K + (Nieves‐Cordones et al ., ), and Cl − with NO 3 − (Wege et al ., ; Wen et al ., ) are also important, as well as unidentified K + transporters that may be important under salinity (Caballero et al ., ). Energy costs of phosphorylation, though important in regulation of transport (Barajas‐Lopez et al ., ), are probably small (Shacter et al ., ).…”
Section: Energy Demandsmentioning
confidence: 99%